2013
DOI: 10.1155/2013/287319
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genotoxic Effects of New Molecules with Possible Trypanocidal Activity for Chagas Disease Treatment

Abstract: Chagas disease is responsible for a large number of human infections and many are also at risk of infection. There is no effective drug for Chagas disease treatment. The Institute of Pharmaceutical Technology at Fiocruz, Brazil, has designed three nitro analogs of the nitroimidazole-thiadiazole, megazol: two triazole analogs PTAL 05-02 and PAMT 09 and a pyrazole analog PTAL 04-09. A set of Salmonella enterica serovar Typhimurium strains were used in the bacterial reverse mutation test (Ames test) to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Our group has investigated new nitroimidazoles as trypanocidal agents and their mutagenic/genotoxic activities. We have observed that these activities do not only depend on the nitro group ( Boechat et al 2001 , Carvalho et al 2004 , 2006 , 2007 , 2008 , 2014 , Mello et al 2013 ). Encouraged by this observation, in the present work we evaluated the genotoxic, mutagenic and antitrypanocidal activities of nine nitroimidazoles (11-19) ( Fig.…”
mentioning
confidence: 83%
“…Our group has investigated new nitroimidazoles as trypanocidal agents and their mutagenic/genotoxic activities. We have observed that these activities do not only depend on the nitro group ( Boechat et al 2001 , Carvalho et al 2004 , 2006 , 2007 , 2008 , 2014 , Mello et al 2013 ). Encouraged by this observation, in the present work we evaluated the genotoxic, mutagenic and antitrypanocidal activities of nine nitroimidazoles (11-19) ( Fig.…”
mentioning
confidence: 83%
“…In relation to compound 6, mutagenicity was reported in the Ames test in TA100 strain of Salmonella typhimurium at the highest tested concentration (50 μg/mL) in the absence and presence of S9 mixture 39 . It showed cytotoxic activity in the concentration of 50 μg/mL in TA98 and in the range of 1.0-50 μg/mL in TA100 and TA1535 strains 39 .…”
Section: Discussionmentioning
confidence: 99%
“…It showed cytotoxic activity in the concentration of 50 μg/mL in TA98 and in the range of 1.0-50 μg/mL in TA100 and TA1535 strains 39 . Our results of the CBMN of 6 in WHBC, recommended by OECD (2016) 30 differed from those obtained by Mello et al 39 who showed a significant increase of MNC in RAW 264.7 cells at concentrations of 10 and 100 μg/mL when treated for a period six times higher than that used in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the damage was significantly higher also in control samples, indicating that the S9 fraction displayed genotoxic properties, its use has been omitted from the following experiments. It has been previously recorded that the S9 fraction itself is able to induce 2–2.5 times more revertants in TA97 and TA98 lines using the Ames test (Mello et al ., ; Sauerborn Klobučar et al ., ). Cells with excessive DNA damage (>50%) that are usually considered as dead or dying cells (e.g.…”
Section: Discussionmentioning
confidence: 99%